Reliability of Position Generator Measures across Different Occupational Lists: A Parallel Test Experiment. Issue 3 (August 2013) - Verhaeghe, Pieter-Paul; Putte, Bart Van de; Roose, Henk
The position generator is a widely used research tool to measure individual social capital. Although the position generator is said to be reliable, there are only a few broad guidelines to construct the instrument and there is no standard list of occupational items. Furthermore, the reliability of the position generator across different occupational lists has not yet been tested. This article examines the reliability of 13 position generator measures across different occupational lists by means of a parallel test experiment. We found that only the volume measure has good reliability. Reliability of the social class–based position generator measures is fair to good, and reliability of the occupational prestige/status–based position generator measures is poor. These latter types of measures are the ones most often used.